2014
DOI: 10.5055/jem.2014.0166
|View full text |Cite
|
Sign up to set email alerts
|

Shelter-in-place and mental health: An analogue study of well-being and distress

Abstract: The results of this study provide evidence to emergency management professionals that SIP is viable disaster response strategy that does not adversely impact mental health provided group cohesion is high. The findings also have implications regarding public messaging and outreach initiatives regarding the emotional and physical safety of SIP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…However, we find that the risk model for transmission of SARS-CoV-2 is nuanced—while the highest risk of transmission is in crowded and enclosed settings, casual social interaction in some public settings have a lower risk. In addition, as the pandemic progresses and concern with physical distancing measures (so-called “quarantine fatigue”) gain momentum [ 109 ], public communications surrounding these measures should convey this continuum of risk based on the transmission dynamics across different settings, supporting sustainable longer-term behavior changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we find that the risk model for transmission of SARS-CoV-2 is nuanced—while the highest risk of transmission is in crowded and enclosed settings, casual social interaction in some public settings have a lower risk. In addition, as the pandemic progresses and concern with physical distancing measures (so-called “quarantine fatigue”) gain momentum [ 109 ], public communications surrounding these measures should convey this continuum of risk based on the transmission dynamics across different settings, supporting sustainable longer-term behavior changes.…”
Section: Discussionmentioning
confidence: 99%
“…(so-called "quarantine fatigue") gain momentum [109], public communications surrounding these measures should convey this continuum of risk based on the transmission dynamics across different settings, supporting sustainable longer-term behavior changes.…”
Section: Plos Onementioning
confidence: 99%
“…In addition, as anxiety with physical distancing measures (so-called "quarantine fatigue") gain momentum (132), public communications surrounding these measures should convey this continuum of risk based on the transmission dynamics across different settings, supporting sustainable longer-term behavior changes.…”
Section: Secondary Attack Ratementioning
confidence: 99%
“…Previous research suggests that those who are quarantined are at increased risk for psychological distress 55 . One study suggested that those who are sheltering at home with their family are not likely to experience marked distress 56 . Providing additional support to staff members who are isolated or quarantined is warranted including strategies such as emphasizing the importance of staying connected with their primary support network, maintaining a sense of meaning and purpose through work to help others either possibly using telemedicine or other outreach efforts and monitoring for symptoms suggestive of post‐traumatic stress disorder.…”
Section: Wellness and Resource Utilizationmentioning
confidence: 99%
“…55 One study suggested that those who are sheltering at home with their family are not likely to experience marked distress. 56 Providing additional support to staff members experiencing the highly stressful combination of caring for very ill patients, being concerned for the well-being of fellow coworkers and potentially facing exposure to the virus themselves. Ultimately, utilizing existing resources including employee assistance programs, physician well-being teams, wellness programs or peer support may enhance staff resilience in the setting of prolonged stress from the pandemic.…”
Section: Medical Distancingmentioning
confidence: 99%